Measuring the technological competitiveness of economies with the PTCE method: PRC vs. USA 2000–2020 - Woźnicki, Adam; Gawlik, Remigiusz (Technological and Economic Development of Economy, 2024)
The relationship between China (PRC) and the United States (USA) has reached an unprecedented level of tension, mainly due to economic and technological rivalry. This study introduces an original quantitative method, the Pentagon of Technological Competitiveness of Economy (PTCE) to measure the technological competitiveness of both countries from 2000 to 2020. The findings reveal that while the USA remains a global technological leader, the PRC is emerging as a formidable challenger. Although the USA still holds the lead, signs of decline are visible, while the PRC exhibits a remarkable upward trajectory in technological competitiveness. The findings provide actionable recommendations for policymakers. To reinforce its position as the unrivaled technological leader, the USA should prioritize enhancing capabilities in areas such as patents, scientific articles and the export of high technology and STEM-related products. For the PRC there is an unprecedented opportunity to surpass the USA in technological leadership by strategic investments in research, innovation and human capital development. The novelty of this research lies in two main areas: (i) its significant contribution to competitiveness analysis through the introduction of the PTCE method and (ii) its provision of a comprehensive assessment of the shifting technological dynamics between the USA and the PRC.